Factors Influencing the Level of Intermediation of Rural Banks in Indonesia 2008:1 – 2010:8 - Jamil, Azimah; Kamio, Kamio; Supadi, Supadi (Lingka Ekonomika, 2024)
This research entitled "Factors Influencing the Level of Intermediation of Rural Banks in Indonesia 2008:1 - 2010:8". This study analyzes a number of variables that affect the banking intermediation in Indonesia during the period January 2008 until August 2010. This study aims to determine the development of intermediation of Rural Bank In Indonesia, which in expressing by Loans to Deposit Ratio ( LDR). The research method is a method of library research by using secondary data. Then the method analysis is multiple linear regression analysis with the classical assumption test (Normality, Multicollinearity, Autocorrelation, Heteroscedasticity and Linearity) and the statistical (goodness of fit test, t test and F test). The result of classical assumption test shows that in regression model statistically there is no Normality, Multicollinearity, Autocorrelation, Heteroscedasticity and Linearity. As the result of multiple linear regression and statistical tests, variables that significant influence the Rural Bank intermediation is Consumer Price Index, variable is a having significant influence on loan is investment loan interest rate, and variable is a having significant influence on third party funds is LPS insured interest rates . The result of his research indicates that the LDR variable (Rural Bank intermediation) is explainable by variation of working capital loan interest rate, investment loan interest rate, consumer loan interest rate, Non Performing Loan (NPL), LPS insured interest rates and Counsumer Price Index (CPI) with the adjusted R-squared coefficient of 0.42. 0.75 for Loan and 0.73 for Third Party Funds. Intermediary function can be said optimal if can reach 80 to 90 percent. From the LDR of Rural Bank in Indonesia value of 83.95 percent in the end of research period can concluded that LDR from 2008:1 to 2010:8 indicates that the Rural Bank intermediation Indonesia is running optimally. Look at research results that show that Consumer Price Indeks (CPI) the most sensitivity factor for banking intermediation, so Whereas In fact Rural Bank has provided non loan consumption, but this fund of loan is more widely utilized by the debtors to in fund beyond their original requirement. In this case Rural Bank in performing its intermediary function should be more selective to the prospective borrowers who want to apply for loan and the allocation of loan.